Manajemen Pokdarwis Berbasis Masyarakat Adat di Desa Wisata Adat Ngadas, Malang - Vincent Alfredo Nathaniel; Nadia Anastasya Nathania; Cheryl Jesslyn Waisa; Budi Setiawan (Nawasena: Jurnal Ilmiah Pariwisata, 2024)
The Ngadas Traditional Tourism Village, which is located in the Tengger region, Malang Regency, is one of the leading tourist attractions based on indigenous communities which manages tourism by combining local wisdom values. The aim of this research is to see how indigenous communities manage Tourism Awareness Groups (Pokdarwis) to support sustainable tourism. Data was collected through observation, interviews and document analysis using a descriptive qualitative approach. The results of the research show that Pokdarwis Ngadas uses an approach that prioritizes preserving local customs and culture, such as Kasada rituals, agricultural traditions, and social procedures. The management model used relies on the participation of indigenous communities in traditional organizations with the guidance of traditional leaders. As a tourism center, this village offers homestays, supports cultural tourism, and encourages ecotourism. The success of this program is supported by good cooperation between indigenous communities and Pokdarwis. However, the challenges faced include dependence on natural resources and the threat of modernization. This research concludes that indigenous community-based Pokdarwis management makes a significant contribution to creating tourism that is inclusive, sustainable and based on cultural preservation. Research recommendations include increasing the capacity of Pokdarwis members through training, human resources, application of Sapta Pesona, and local community efforts.